EFFECT OF LOCOMOTOR TRAINING WITH BODY WEIGHT SUPPORT ON GAIT AND LOWER LIMB STRENGTH IN INCOMPLETE SPINAL CORD INJURY-A CASE REPORT (International Journal of Physiotherapy, 2016)
Background: Irrespective of the severity of the spinal injury, time after lesion and age at time of injury, the restoration of walking is given high priority by subjects with SCI. There is ample amount of literature with gait training methods for restoration of locomotion from other parts of the world. Rehabilitative training is currently one of the most thriving treatments to promote functional recovery following SCI. Many strategies exist to enhance locomotion, such as treadmill training with and without body weight support, robotic-assisted gait training, functional electrical stimulation, epidural stimulation and surface spinal stimulation. Pertaining to developing countries, this case study is an attempt to determine the effect of Locomotor Training with Body Weight Support on Gait and Muscle Strength in IncompleteSpinal Cord Injury.Methods: Single case design, Body weight support treadmill training for over a period of 12 months for an Individual with SCI (ASIA C) in a private clinic set up for SCI rehabilitation. ASIA lower extremity muscle strength, Spinal Cord Injury Functional Ambulation Inventory and Walking Index for Spinal Cord Injury –II.Results: Significant change in lower extremity muscle strength, gait parameters and temporal parameters of SCI-FAI. Though, no change was observed in score of assistive devices and similarly WISCI-II scoring.Conclusion: Single participant case study provided us with vital evidence for locomotor training with Body weight support in incomplete SCI. Further research in to the field shall yield valuable clinical findings.